Embedding of psycho-perceptual-motor skills can improve athlete assessment and training program - Müller, S.; van Rens, F.; Brenton, J.; Morris-Binelli, K.; Piggott, B.; Rosalie, S.M.; Burgin, M. (Journal of Expertise, 2019)
Practitioners in a variety of sports seek unique ways to train athletes to better prepare them for competition. In this position paper, we argue that inclusion of psycho-perceptual-motor skills, from the fields of sport psychology and sport expertise, is crucial, but underutilized in the assessment and training of athletes. First, a brief introduction is provided as to why psycho-perceptual-motor skill is vital for training athletes. Second, examples are discussed relating to key concepts. These include the following: assessment of expertise discriminators such as visual anticipation under pressure contexts, incorporation of sports analytics and performance analysis to aid reflection upon previous experiences of good anticipation and coping with pressure, use of qualitative and quantitative measures to understand processes underlying performance and learning, as well as design of representative tasks for assessment and training anticipation under pressure contexts. Third, some recommendations are made to practitioners of sports teams to assist them in taking advantage of psycho-perceptual-motor skill to better prepare athletes for competition. Collectively, we hope this paper stimulates collaboration between practitioners of sports teams and scientists to create a greater focus upon integrated sport psychology and sport expertise in the training of athletes.